Neurotrophic corneal ulcer and iridocyclitis directly preceding Ramsay-Hunt Syndrome - Farzan M. Gorgani, MS, DO. (Elsevier, 2021)
Purpose: To present to and inform the practitioner of an unusual presentation of Varicella zoster virus and Ramsay-Hunt Syndrome. Observations: A 69-year-old bedbound male with vascular dementia presented to the emergency room with a red right eye with associated tearing and mucus production. The patient could not express if he was in pain. The initial diagnosis from the emergency room was bacterial keratitis, confirmed with a positive pseudomonas culture. However, upon examination by the ophthalmologist it was noted that there was not only a large, infected epithelial defect, but also an intraocular pressure of 35 and a candy-cane hypopyon. The diagnosis of herpes neurotrophic keratitis and iridocyclitis was made and the patient was started on intravenous acyclovir along with the appropriate topical medications. A day later, it was noted that the patient developed a right sided facial palsy and vesicular lesions inside the right ear canal, as confirmed by otolaryngology. Conclusion and Importance: Ramsay-Hunt Syndrome is usually known to the ophthalmologist due to the exposure keratopathy caused by facial palsy. This case demonstrates varicella-zoster virus (VZV) neurotrophic keratitis preceding the development of facial palsy, which can further exacerbate an already neurotrophic cornea. The practitioner should be aware of these signs and symptoms and adjust their treatment with systemic acyclovir-prednisone.